La motivación del ser en el acto migratorio de un venezolano que no cuenta con un trabajo formal en la ciudad de Bogota, Colombia (2020)
In this research, a case study was carried out on how a Venezuelan migrant with economic difficulties due to labor issues satisfies deficit needs and acquires growth characteristics. For this purpose, a qualitative methodology was used in which the clearest theoretical reference is the Theory of the hierarchy of needs attached to an epistemological basis of humanistic psychology, the technique used to collect the information was an open interview. The analysis allowed us to describe how the satisfaction of the needs of the subject suffered some mishaps due to adverse situations, and how migration mainly affects the satisfaction of the need for affection and a sense of belonging; and that in turn also influences others, such as the difficulty of acquiring growth characteristics, but despite this, the motivation of his family generates other links that allow them to acquire these characteristics.